Compact operational tropospheric water vapor and temperature Raman lidar with turbulence resolution datasets - Diego Lange; Andreas Behrendt; Volker Wulfmeyer (PANGAEA, 2019)
We present the new Atmospheric Raman Temperature and Humidity Sounder (ARTHUS). We demonstrate that ARTHUS measurements resolve 1) the strength of the inversion layer at the planetary boundary layer top, 2) elevated lids in the free troposphere during daytime and nighttime, and 3) turbulent fluctuations in water vapor and temperature, simultaneously, also during daytime. Very stable and reliable performance was demonstrably achieved during more than 2500 hours of operations time experiencing a huge variety of weather conditions. ARTHUS provides temperature profiles with resolutions of 10-60 s and 7.5-100 m vertically in the lower free troposphere. During daytime, the statistical uncertainty of the WV mixing ratio is <2 % in the lower troposphere for resolutions of 5 minutes and 100 m. Temperature statistical uncertainty is <0.5 K even up to the middle troposphere. ARTHUS fulfills the stringent WMO breakthrough requirements on nowcasting and very short-range forecasting.